The put-em-rights - Blyton, Enid; Rothera, Chris (Nottinghamshire Award Publications, limited, 2010)
The Put-Em-Rights are a secret band of do-gooders. Sally, Amanda, Micky, Podge, Yolande and Bobby are all eager to solve everyone's problems. But it's not always easy trying to help without getting into lots of trouble...They also find there are some things about themselves which need putting right too!